HDRPS+: a new affective pictorial scale applicable to organizational contexts - Ping Liu; Ya’Nan Wang; Ya’Nan Wang; Yanlin Liu; Jiangning Hu; Yunyi Li; Ke Zhao; Jian’guo Mao (Frontiers in Psychology)
IntroductionRepeatedly capturing individuals’ emotions is challenging in organizational settings, especially for low-literacy groups, and existing pictorial scales cover arousal only narrowly. We therefore developed the Highly Dynamic and Reusable Picture-based Scale Plus (HDRPS+), an optimized successor to HDRPS that measures valence and arousal simultaneously.MethodsThree sub-studies were conducted. (1) Picture pool construction: 20 thematic images were created to span the affective space. (2) Picture screening: crowdsourced ratings anchored each image’s valence -arousal coordinates. (3) Validation: a 7-day diary study with 442 participants (age 13-69, M = 27.06) tested reliability and validity.ResultsHDRPS+ achieved good user retention, with 80.3 % of participants providing data on at least five days. It also showed acceptable stability (consistency = 0.69 valence, 0.65 arousal) without materially influencing the affect it is intended to measure. Correlations with the Self-Assessment Manikin (SAM) confirmed concurrent validity (r = 0.63 for valence; 0.52 for arousal), while all coefficients with PANAS were < 0.45, supporting discriminant validity. Participants judged the scale accurate or very accurate in 78 % of cases, and indirect checks (vs. SAM) indicated reduced social_desirability bias.DiscussionHDRPS+ is low_cost, quick, and well_tolerated, enabling continuous affect tracking in diverse organizational settings. Future work should keep refining emotional granularity, broaden application formats, and test cross_cultural use. HDRPS+ images with normative scores are available at https://osf.io/d4wcn.